2020
DOI: 10.3390/cells9051173
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of microRNA in Adult Rat Heart with Isoproterenol-Induced Cardiac Hypertrophy

Abstract: Cardiac hypertrophy is a common pathological condition and an independent risk factor that triggers cardiovascular morbidity. As an important epigenetic regulator, miRNA is widely involved in many biological processes. In this study, miRNAs expressed in rat hearts that underwent isoprenaline-induced cardiac hypertrophy were identified using high-throughput sequencing, and functional verification of typical miRNAs was performed using rat primary cardiomyocytes. A total of 623 miRNAs were identified, of which 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 64 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…The excessive ROS derived from NADPH oxidases activates various hypertrophy-related signaling pathways, for example, the MAPK signaling pathway [ 43 ]. Treatment with ISO has been reported to activate the MAPK signaling pathway [ 44 ], composed of P38, JNK, and ERK. The signaling pathway regulates a variety of biological behaviors, including cell proliferation, differentiation, and apoptosis [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The excessive ROS derived from NADPH oxidases activates various hypertrophy-related signaling pathways, for example, the MAPK signaling pathway [ 43 ]. Treatment with ISO has been reported to activate the MAPK signaling pathway [ 44 ], composed of P38, JNK, and ERK. The signaling pathway regulates a variety of biological behaviors, including cell proliferation, differentiation, and apoptosis [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathological increase in the concentration of circulating catecholamines and their excessive release from the cardiac sympathetic nerve endings lead to direct damage to the cardiomyocytes [30]. The pathophysiological mechanisms involved in catecholamineinduced myocardial injury include increased oxygen demand of the cardiomyocytes with insufficient supply, oxidative stress, calcium overload, myofibril over-contraction, and upregulation of the expression and release of inflammatory cytokines [31][32][33][34][35][36][37][38][39][40][41][42]. Indeed, histopathological examinations of the myocardium of rats treated with supraphysiological doses of catecholamines showed focal necrosis and degeneration of the cardiomyocytes, disordered myofibrils, advanced cytoplasmic vacuolization, myocardial infiltration with inflammatory cells, and tissue fibrosis [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…The knockout of LATS1/2 in the epicardium of mouse embryos is embryonically lethal, resulting in defective coronary arteries ( Singh et al, 2016 ; Xiao et al, 2018 ). Gan M. et al (2020) reported that p-LATS1/2 inhibits mTORC1 signaling to control heart size by directly phosphorylating S606 of Raptor to attenuate mTORC1 kinase activation.…”
Section: Ncrna/hippo Pathway In Cardiac Developmentmentioning
confidence: 99%